Interações entre sociedade e Floresta com Araucárias: aspectos socioeconômicos e conservação ambiental - Schú, Aline (2019)
This study reports some forms of interactions between society and Forest with Araucarias, which occurred from the beginning of the twentieth century to the present period, in the region of Carazinho, Rio Grande do Sul, Brazil. The forms of exploitation of the forest are approached, especially the Brazilian pine Araucaria angustifolia (Bertol.) Kuntze 1898, its logistics in the national and international markets, the relevant legislation, the organization of loggers in unions and cooperatives, the replacement of Brazilian pine and the performance of the National Pine Institute (INP). In Carazinho, the planting of araucarias was carried out in an area that belonged to the Forest Cooperative and was expropriated in 1967 for the municipality. Space, over the years, has become a protected area. An Environmental History of the João Alberto Xavier da Cruz Municipal Natural Park was built and related to an Environmental History of the municipality. A guided interpretive trail was applied in the form of a pilot test, which was based on these Environmental Stories and was built with the help of society. The perceptions of ten respondents about the protected area were analyzed. The research used bibliographies and documents, mainly newspapers, and oral history. In the 1930s to 1950s, there was little concern for environmental conservation. Newspapers showed the rapid transformation of the landscape and the Araucaria Forest was exposed to a great loss of biodiversity. The efforts of society, the press and organizations, such as the Association of Friends of the Environment, were indispensable for the effectiveness of the Park as a conservation unit. The neglect of public managers over the years has contributed to some inappropriate uses of the place. The guided interpretative trail contributed to the acquisition of knowledge and was included in the Public Use Program of the conservation unit, which demonstrated the appreciation of the proposal built with society by the municipal government. The Park is constituted as historical and environmental patrimony of the municipality.